1D/3D Finite-Volume coupling in conjunction with beam/shell elements coupling for fast transients in pipelines with fluid–structure interaction. (February 2021) - Daude, F.; Galon, P.; Douillet-Grellier, T.
Abstract: A 1D/3D Finite-Volume coupling is proposed for the Euler/Homogeneous Equilibrium Model equations. The present approach is based on the Finite-Volume framework making it possible to tackle general equations of state. A special attention is given to the conservation of mass, momentum and energy at the common 1D/3D interface. For fluid–structure interaction induced by fast-transient phenomena occurring in pipelines, the present 1D/3D fluid coupling is also associated with a beam/shell elements coupling to deal with the mechanical pipe behavior. A series of test-cases involving both purely fluid, purely structural and coupled fluid–structure problems with available analytical or experimental references is considered to demonstrate the performance of the present 1D/3D coupling.